Nonlinearities in the cellular response to ionizing radiation and the role of p53 therein. (3rd August 2021) - Murray, David; Mirzayans, Razmik
Abstract: Many aspects of the cellular response to agents such as ionizing radiation that cause genotoxic and/or oxidative stress exhibit a nonlinear relationship to the applied stress level. These include elements of the antioxidant response and of the damage-signaling pathways that determine cell fate decisions. The wild-type p53 protein, which is mutated in many cancers, coordinates these responses and is a key determinant of this nonlinearity. Indeed, p53 has been referred to as a 'cellular rheostat' that favors antioxidant/cytoprotective functions at low stress levels while switching to a pro-oxidant/cytotoxic role under high-stress conditions. For solid tumor-derived cell lines, moderate doses of radiation, typical of those used to generate clonogenic survival curves (i.e. ≤10 Gy), predominantly invoke a dose-dependent cytostatic response. For cancer cell lines with wild-type p53, cytostasis is primarily associated with features of senescence, whereas cancer cells with aberrant p53 primarily undergo endopolyploidization and enlargement. In line with a commentary by Meyn et al. [Int J Radiat Biol. 2009, 85:107–115] concluding that apoptosis is not the primary cause of radiation-induced loss of clonogenicity in solid tumor-derived cell lines, significant levels of apoptosis are typically seen only after higher doses (≥5 Gy) and this is almost all of the delayed (rather than primary) type. Nonlinearity of the oxidative/genotoxic stress response is already apparent in the early antioxidant events activated by transcription factors such as p53 and Nrf2 and the Ref1 transcription coactivator. These cytoprotective pathways serve to minimize damage to important cellular targets caused by reactive oxygen species (ROS) and other electrophiles. After high/supra-lethal levels of stress these inducible antioxidant pathways can be deactivated in a manner that would reinforce the establishment of the pro-oxidant state, resulting in elevated ROS levels and to cytostasis or apoptosis. Understanding the complex regulation of these damage-signaling pathways in relation to the stress levels is important for the optimal utilization of radiation therapy for cancer.